2008
DOI: 10.1890/08-0363.1
|View full text |Cite
|
Sign up to set email alerts
|

The Legacy of Mercury Cycling From Mining Sources in an Aquatic Ecosystem: From Ore to Organism

Abstract: Clear Lake is the site of an abandoned mercury (Hg) mine (active intermittently from 1873 to 1957), now a U.S. Environmental Protection Agency Superfund Site. Mining activities, including bulldozing waste rock and tailings into the lake, resulted in approximately 100 Mg of Hg entering the lake's ecosystem. This series of papers represents the culmination of approximately 15 years of Hg-related studies on this ecosystem, following Hg from the ore body to the highest trophic levels. A series of physical, chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(66 citation statements)
references
References 62 publications
(77 reference statements)
2
64
0
Order By: Relevance
“…87 The mass of IHg in surface organic matter is likely very small relative to Hg from mine waste in the watershed (e.g., ~100 Mg of Hg is stored upstream in Clear Lake). 70 It was previously observed that MMHg concentrations in Cache Creek biota increase with distance from upstream reservoirs 11 and methylation in Cache Creek is thought to be promoted by in situ geochemical conditions such as high sulfate. 11,66,88 Other studies have suggested IHg in streams can be methylated in hyporheic zones 89 or when associated with epilithic periphyton 90 or filamentous algae.…”
Section: Cache Creekmentioning
confidence: 97%
“…87 The mass of IHg in surface organic matter is likely very small relative to Hg from mine waste in the watershed (e.g., ~100 Mg of Hg is stored upstream in Clear Lake). 70 It was previously observed that MMHg concentrations in Cache Creek biota increase with distance from upstream reservoirs 11 and methylation in Cache Creek is thought to be promoted by in situ geochemical conditions such as high sulfate. 11,66,88 Other studies have suggested IHg in streams can be methylated in hyporheic zones 89 or when associated with epilithic periphyton 90 or filamentous algae.…”
Section: Cache Creekmentioning
confidence: 97%
“…Clear Lake is a large (177 km 2 ), shallow, eutrophic, polymictic lake in the central Coast Range of northern California, USA, that has been subjected to multiple stresses from natural and anthropogenic sources (Suchanek et al 2003(Suchanek et al , 2008d. One of the most prominent stressors has been Hg contamination from an abandoned mine along its shoreline, although pesticide applications, eutrophication, and alien species introductions have also dramatically impacted the lake's ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Natural stressors on this ecosystem have included geologic and tectonic events (some changing the entire flow regime of the lake), regional and global climate change, fires, droughts, and floods. Anthropogenic stressors have included logging and deforestation, dam construction, fire, wetland destruction, livestock over-grazing, and numerous mining operations, the largest being Hg mining (see Suchanek et al 2003Suchanek et al , 2008d.…”
Section: Introductionmentioning
confidence: 99%
“…The lake, which is described elsewhere (Suchanek et al 2003, was selected for an ecosystem-scale investigation of Hg cycling and effects for several reasons. First, the dominant source of Hg in the lake was (and remains) the now-inactive Sulphur Bank Mercury Mine (Suchanek et al 2008e;Suchanek et al, in press). During operation of the mine, Hg-laden tailings and waste rock that were not of sufficient quality for processing were bulldozed into the lake for disposal (Suchanek et al 2008a, e).…”
Section: The Clear Lake Studymentioning
confidence: 99%
“…Data were compiled from the Department of Conservation (California Geological Survey, Sacramento) and the U.S. Geological Survey (Sacramento). Lake Hg investigation is provided by Suchanek et al (2008e).…”
Section: Introductionmentioning
confidence: 99%